Types and Reasons for Code-Switching Used by Andovi Da Lopez in AndoviAndreasShow - Sang Ayu Made Sheera Uzziela (Kata Kita: Journal of Language, Literature, and Teaching, 2024)
This study aims to discover the types and reasons for code-switching used by Andovi Da Lopez in the AndoviAndreasShow. This study wants to identify what types and why Andovi Da Lopez used code-switching during his conversation in the three videos in AndoviAndreasShow. The writer used Hoffmann's (2014) theory of code-switching types (Intra-sentential switching, Inter-sentential switching, and Emblematic switching) as well as Holmes and Wilson's (2017) theory of code-switching reasons (Participants, solidarity, and status, Topic, Switching for Affective Functions, Metaphorical Switching, Lexical Borrowing, Linguistic Constraints). This study used the descriptive qualitative method. The data collected showed that all code-switching types complied with Hoffmann's (2014) theory. Furthermore, Andovi Da Lopez just used five reasons stated by Holmes and Wilson (2017) in the AndoviAndreasShow videos.